Analisis Sistem Penyediaan Air Bersih di PDAM Tirta Silau Piasa, Kisaran Barat, Asahan, Sumatra Utara - Surya Budi Lesmana , Ramadhan Saragih (Semesta Teknika, 2013)
Water supply in Indonesia is facing some problems, such as lack of available water resources, lack of water supply services to the whole community and many water sources are polluted. In this study the water supply system in PDAM Tirta Silau Piasa was analyzed, and the results are used as input data for the evaluation of pipeline simulation using Waternet Software. Results of this study showed that the pipe for water distribution will still function properly until 2015 .